The Administrative Law Problems in Recording Marriage Which No Recorded in The Family Card (KK) - Moh Taufik; Najmudin Najmudin (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This research aims to know how regulations recording marital status with no recorded in family card at the Population & Registration Service Civil Office & Problems law what will appear related policy recording marital status No recorded in Family card Service Population & Recording Civil especially in Sudur from the point of view of State Administrative Law. This study use literature approach and juridical normative, with use draft marriage & compatibility between Law of Marriage & Regulation Minister In Country. As material study is primary & secondary materials as well as source person in study This is Office Ministry Religion & Population & Registration Service Civil. Writing marital status with no recorded as effort for ensure order law as instrument certainty law through proof marriage contradictory with obligation recording the marriage arranged in Law No. 1 of 1974 about Marriage. Need exists umbrella parallel law in sequence legislation in Indonesia, so policy This not legally biased in a way state Administration.